2008
DOI: 10.1021/ol702830p
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II)-Directed Self-Assembly of Dynamic Donor−Acceptor [2]Catenanes

Abstract: Highly efficient syntheses of donor-acceptor [2]catenanes were developed using a combination of templation and reversible metal-ligand coordination. The desired [2]catenanes were obtained within minutes through a five-component assembly, involving a donor-containing crown ether, an acceptor-containing ligand, two Pd(II) metal centers, and a dipyridyl ligand. The [2]catenane formation was characterized by 1H NMR and UV-vis spectroscopies and cold-spray ionization mass spectrometry. In particular, great translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(17 citation statements)
references
References 34 publications
0
14
0
3
Order By: Relevance
“…[21] Supramolecular multicomponent (n ! 4) self-assemblies, built on more than two different reversible interactions, are still remarkable exceptions, [22] in particular if they form in a quantitative manner. Every additional orthogonal interaction will furthermore open up a multitude of new chances.…”
mentioning
confidence: 99%
“…[21] Supramolecular multicomponent (n ! 4) self-assemblies, built on more than two different reversible interactions, are still remarkable exceptions, [22] in particular if they form in a quantitative manner. Every additional orthogonal interaction will furthermore open up a multitude of new chances.…”
mentioning
confidence: 99%
“…In 2008, Liu et al reported the efficient synthesis of [2]catenanes 3-5 by exploiting favourablep arameters, such as donor-acceptor templating and dynamic palladium(II)-pyridine coordination (Scheme 1). [10] [2]Catenane 3 is composed of one unit of CE1 interlocked with ah eteroleptic complex [Pd 2 (en) 2 (L3)(L4)](NO 3 ) 4 (PF 6 ) 2 .C atenane 3 was obtained by mixing cis-[Pd(en)(NO 3 ) 2 ], ad icationic bidentate ligand L3 crafted with an acceptorm oiety of 4,4'-bipyridine ligand L4,a nd CE1 crafted with two donor moieties in ar atio of 2:1:1:1i n acetonitrile/water (1:1) at room temperature. The in situ formed D-shaped macrocycle provides ar ectangular cavity that is optimal for an alternatea rrangement of the donor-acceptor p systems present in the bound ligandsa nd crown ether (Scheme 1).…”
Section: Binuclear Assemblies From Bidentateligandsmentioning
confidence: 99%
“…4) mit mehr als zwei unterschiedlichen reversiblen Wechselwirkungen sind immer noch bemerkenswerte Ausnahmen, [22] insbesondere wenn sie quantitativ in eine einzige Struktur münden. Jede weitere orthogonale Wech- selwirkung wird zudem eine Vielfalt neuer Möglichkeiten eröffnen.…”
unclassified
“…[21] Supramolekulare Mehrkomponenten-Selbstassemblierungen (n ! 4) mit mehr als zwei unterschiedlichen reversiblen Wechselwirkungen sind immer noch bemerkenswerte Ausnahmen, [22] insbesondere wenn sie quantitativ in eine einzige Struktur münden. Jede weitere orthogonale Wech-[*] Prof.…”
unclassified
See 1 more Smart Citation